The Impact of SARS-CoV-2 on the Most Common Comorbidities–A Retrospective Study on 814 COVID-19 Deaths in Romania - Barbu, Madalina Gabriela; Thompson, Richard James; Thompson, Dana Claudia; Cretoiu, Dragos; Suciu, Nicolae (Frontiers in Medicine, 2020)
Background: The SARS-CoV2 infection has rapidly spread throughout the world, particularly affecting those with underlying conditions. Objective: To assess the impact of SARS-CoV-2 on the most prevalent comorbidities, among people who died of COVID-19 in Romania. Methods: The study comprised 814 deaths caused by COVID-19 between 22nd March and 8th May, 2020 as reported by the Ministry of Health. WHO data regarding deaths of the general population of Romania was used for comparison. The study analyzed the demographics, number and prevalence of comorbidities and calculated the relative risk for each comorbidity. Results: The study sample consisted of 61.4% males and 38.6% females; the mean age was 68.2y; 90.9% of deaths occurred in people 50+ years. The mean number of pre-existing conditions was 2.73 (SD=1.521), with 97.4% of the patients having at least one. The most prevalent comorbidities were hypertension (43.1%), diabetes (33.2%) and coronary heart disease (26.0%). The calculated relative risk of dying due to COVID-19 was divided into 3 risk categories: high impact comorbidities (RR>3) included diabetes RR=6.426 (95% CI 4.965-8.318), chronic renal disease RR=4.338 (95% CI 3.556-5.292) and hypertension RR=3.261 (95% CI 2.687-3.958). The medium impact (RR=2-3) group comprised chronic pulmonary disease RR=2.615 (95% CI 2.061-3.319) and chronic liver disease RR=1.577 (95% CI 1.183-2.104) and the low impact group (RR<2) - coronary heart disease RR=0.664 (95% CI 0.581-0.758), cancer RR=0.515 (95% CI 0.416-0.637) and stroke RR=0.468 (95% CI 0.370-0.593). Conclusion: SARS-CoV-2 had a greater impact on people with diabetes, chronic renal disease and hypertension and a lesser impact on those with coronary heart disease, cancer and stroke. Therefore, policies should focus on shielding people in the high-risk group and prioritizing them for vaccination, whilst encouraging those in the low risk group to continue seeking treatment for their underlying disease.